Covering Fuzzy Rough Sets via Variable Precision - Mohammed Atef; A. A. Azzam (Journal of Mathematics)
Lately, covering fuzzy rough sets via variable precision according to a fuzzy γ-neighborhood were established by Zhan et al. model. Also, Ma et al. gave the definition of complementary fuzzy γ-neighborhood with reflexivity. In a related context, we used the concepts by Ma et al. to construct three new kinds of covering-based variable precision fuzzy rough sets. Furthermore, we establish the relevant characteristics. Also, we study the relationships between Zhan’s model and our three models. Finally, we introduce a MADM approach to make a decision on a real problem.